Біологічні особливості проростання насіння рододендронів (Rhododendron L.) в умовах інтродукції - Tymchyshyn, G.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
Laboratory germination as well as its energy by 53 taxons of Rhododendron L. were studied. The best conditions of seeds germination were estimated. The conclusion, that the Rhododendron seeds, introduced in Botanical Garden of Lviv National University, has got high sewing peculiarities and does not need special for-sewing preparations, was made.